(untitled) (Revista Apotheke, 2022)
This article sought to share the experience of a Visual Arts teaching internship experience in a 1st-year high school class in the Visual Arts curriculum component of the ’Aplicação’ school at the Federal University of Pernambuco, having a focus on women artists. The young women artist creation process in the Pernambuco art scene, especially the works of Rayellen Alves and Priscilla Melo, together with the study of the concepts "Intersectionality" and "Place of Speech", within a decolonial and anti-racist pedagogical perspective, guided the semester planning, which had as its starting point the question raised by a student in the classroom: “Are there artists on the periphery, professor?!”, also mobilizes the title of this article. Throughout digital photocollage, students could articulate the discussions experienced in their artistic expressions and practices.